Corrigendum to "NEMO on the shelf: assessment of the Iberia–Biscay–Ireland configuration" published in Ocean Sci., 9, 745–771, 2013 - C. Maraldi; J. Chanut; B. Levier; N. Ayoub; P. De Mey; G. Reffray; F. Lyard; S. Cailleau; M. Drévillon; E. A. Fanjul; M. G. Sotillo; P. Marsaleix (Ocean Science, 2013)

NEMO on the shelf: assessment of the Iberia–Biscay–Ireland configuration - C. Maraldi; J. Chanut; B. Levier; N. Ayoub; P. De Mey; G. Reffray; F. Lyard; S. Cailleau; M. Drévillon; E. A. Fanjul; M. G. Sotillo; P. Marsaleix (Ocean Science, 2013)
This work describes the design and validation of a high-resolution (1/36°) ocean forecasting model over the "Iberian–Biscay–Irish" (IBI) area. The system has been set-up using the NEMO model (Nucleus for European Modelling of the Ocean). New developments have been incorporated in NEMO to make it suitable to open- as well as coastal-ocean modelling. In this paper, we pursue three main objectives: (1) to give an overview of the model configuration used for the simulations; (2) to give a broad-brush account of one particular aspect of this work, namely consistency verification; this type of validation is conducted upstream of the implementation of the system before it is used for production and routinely validated; it is meant to guide model development in identifying gross deficiencies in the modelling of several key physical processes; and (3) to show that such a regional modelling system has potential as a complement to patchy observations (an integrated approach) to give information on non-observed physical quantities and to provide links between observations by identifying broader-scale patterns and processes. We concentrate on the year 2008. We first provide domain-wide consistency verification results in terms of barotropic tides, transports, sea surface temperature and stratification. We then focus on two dynamical subregions: the Celtic shelves and the Bay of Biscay slope and deep regions. The model–data consistency is checked for variables and processes such as tidal currents, tidal fronts, internal tides and residual elevation. We also examine the representation in the model of a seasonal pattern of the Bay of Biscay circulation: the warm extension of the Iberian Poleward Current along the northern Spanish coast (Navidad event) in the winter of 2007–2008.

Towards a regional ocean forecasting system for the IBI (Iberia-Biscay-Ireland area): developments and improvements within the ECOOP project framework - S. Cailleau; J. Chanut; J.-M. Lellouche; B. Levier; C. Maraldi; G. Reffray; M. G. Sotillo (Ocean Science, 2012)
The regional ocean operational system remains a key element in downscaling from large scale (global or basin scale) systems to coastal ones. It enables the transition between systems in which the resolution and the resolved physics are quite different. Indeed, coastal applications need a system to predict local high frequency events (inferior to the day) such as storm surges, while deep sea applications need a system to predict large scale lower frequency ocean features. In the framework of the ECOOP project, a regional system for the Iberia-Biscay-Ireland area has been upgraded from an existing V0 version to a V2. This paper focuses on the improvements from the V1 system, for which the physics are close to a large scale basin system, to the V2 for which the physics are more adapted to shelf and coastal issues. Strong developments such as higher regional physics resolution in the NEMO Ocean General Circulation Model for tides, non linear free surface and adapted vertical mixing schemes among others have been implemented in the V2 version. Thus, regional thermal fronts due to tidal mixing now appear in the latest version solution and are quite well positioned. Moreover, simulation of the stratification in shelf areas is also improved in the V2.

pUL25 immunolocalization in human cytomegalovirus-infected and gene-transfected cells - N. Zini; S. Santi; M. Riccio; M. P. Landini; M. C. Battista; N. M. Maraldi (Archives of Virology, 2000)